Journal of technical education seience No.43 (Ho Chi Minh city Ho Chi Minh city University of Technology and Education, 2017)
Contents: Multi-objective optimization for microwave vacuum drying process of durian; Si nanowires grown by al-catalyzed plasrma-enhanced chemical vapor deposition (pecvd) on quartz substrates for solar cell applications; Performance evaluation of membrane bioreactor for pollutantant removal from domestic wastewater;...